ISOLATION AND MOLECULAR CHARACTERIZATION OF MYCOPLASMA SYNOVIAE FROM INFECTED CHICKENS WITH RESPIRATORY SIGNS. - & et al., Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The aim of this study was to investigate the presence of Mycoplasma synoviae in broiler and layer chickens infected with respiratory signs. A total of 80 samples were collected randomly from layer and broiler chickens with respiratory signs in Baghdad from the period between January to May 2017 from the trachea, Lung, Air sac, oviduct, tracheal swabs, conjunctiva swabs, choanal swabs, and nasal swabs and cultured in PPLO medium with supplements, then positive culture subjected to DNA extracted and Polymerase Chain Reaction assay (PCR) to detect Mycoplasma as a genus and Mycoplasma spp by using specific primers targeting16S rRNA gene. The results of culture revealed that the total rate of Mycoplasma isolates was19/80(23.75%). DNA was extracted from 19 positive isolates, all nineteen isolates were positive for Mycoplasma genus by conventional PCR assay, and a product of 270 bp was generated by amplification of the 16SrRNA gene, while a 210 bp region of 16S rRNA gene was amplified for the Mycoplasma synoviae in 19 isolates. The products of amplification of Mycoplasma synoviae16SrRNA gene was sent to MACROGEM (Korea) for sequencing, then submitted in the Gene bank database and have accession number:ID: MG846121.1. Sequencing alignment showed that local MS isolates had highly identical with standard references at gene bank, analysis the phylogenetic tree revealed the presence of 100% identity of the Iraqi isolate to the USA: West Virginia, United Kingdom, Australia, and Brazil, also had 99% identity to South Africa, China, Sweden, USA, and VitNamHatey. This result was concluded that circulation of the Mycoplasma synoviae among birds of the flock and caused respiratory signs in chickens.